2003
DOI: 10.1038/oby.2003.48
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Serum Adiponectin and Leptin Concentrations with Body Fat Distribution in Humans

Abstract: STAIGER, HARALD, OTTO TSCHRITTER, JÜ RGEN MACHANN, CLAUS THAMER, ANDREAS FRITSCHE, ELKE MAERKER, FRITZ SCHICK, HANS-ULRICHHÄ RING, AND MICHAEL STUMVOLL. Relationship of serum adiponectin and leptin concentrations with body fat distribution in humans. Obes Res. 2003;11:368 -376. Objective: We investigated whether serum concentrations of adiponectin are determined by body fat distribution and compared the findings with leptin. Research Methods and Procedures: Serum concentrations of adiponectin and leptin were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
127
3
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(165 citation statements)
references
References 24 publications
22
127
3
13
Order By: Relevance
“…In another study, fasting serum adiponectin was found not to correlate with hip circumference independently of gender and body fat percent in a mixed population of men and women, although it correlated inversely with WHR. 40 Combined with the present results, this indicates that lower-body fat rather than other factors associated with hip circumference is responsible for variations in plasma adiponectin levels.…”
Section: Discussionsupporting
confidence: 82%
“…In another study, fasting serum adiponectin was found not to correlate with hip circumference independently of gender and body fat percent in a mixed population of men and women, although it correlated inversely with WHR. 40 Combined with the present results, this indicates that lower-body fat rather than other factors associated with hip circumference is responsible for variations in plasma adiponectin levels.…”
Section: Discussionsupporting
confidence: 82%
“…Th ey have performed analysis of several obesity studies and plasma adiponectin levels in healthy adults and rejected a hypothesis that obesity may independently aff ect plasma adiponectin. Th e insignifi cant negative eff ect of WHR, SCWBF, and WC in predicting adiponectin concentration (shown in Table 3) is in agreement with the study being done to investigate the relationship of serum adiponectin concentrations with body fat distribution which reported a negative correlation between WHR as well as WC and adiponectin (Staiger et al 2003). Our fi ndings indicate that BMI, WF, VF, and SCWBF are poor predictors for the considering of the salivary adiponectin concentrations in the healthy adult males.…”
Section: Discussionsupporting
confidence: 79%
“…Some studies have reported a signifi cant association between the adiponectin level with BMI and the fat distribution (Staiger et al 2003;Goropashnaya et al 2009). However, a lack of association of adiponectin with BMI has been also reported by others (Kuo and Halpern 2011).…”
mentioning
confidence: 99%
“…17 We assessed the impact of two common ADIPOQ variants (located in the 5 0 region) on corpulence and body fat distribution in a large cohort of 837 unrelated middle-aged French subjects that were prospectively followed up for 7 years.…”
Section: Discussionmentioning
confidence: 99%